The resurgence of populism in Latin America - Barr, Robert R. (Robert Rennie) (Lynne Rienner Publishers, Inc., 2017)
Latin America has recently experienced a powerful resurgence of populism, a phenomenon that has had an outsized influence on the region's politics. What explains this resurgence? And what is distinctive about this new populist era? Answering these questions, Robert Barr offers a refined conceptualization of populism and an intriguing explanation of its recent electoral successes across the continent.